The Influence of Leachate Water on Corrosion Rate of Mild Steel Plate - Ghofur, Abdul; Rachman, Dhonie Adetya; Lutfi, Muhammad Mochtar; Rahman, Fathur (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
Leachate water from final waste landfill (Tempat Pembuangan Akhir, TPA) contains harmful substances for the environment and living organisms. Furthermore, the leachate water can deteriorate equipment buried near TPA, e.g. buried water pipe. This work investigated the corrosion rate of mild steel SPCC SD after immersion in leachate water of TPA Gunung Kupang and Cahaya Kencana located in South Kalimantan. The steel plate immersion into leachate water was worked out in 3 different cases. The first case was 2 weeks immersion in leachate water followed by 1 week contact with ambient air. In the second case, steel plate was immersed in leachate water for 1 week and then 2 weeks in direct contact with ambient air. The last one was steel plate immersion in leachate water for 3 weeks without any direct contact with ambient air. The investigation shows that longer contact duration between wet steel surface, after immersion in leachate water, with ambient air increases the corrosion rate. The investigation shows also that the corrosion rate due to leachate water from Gunung Kupang landfill is higher than that of Cahaya Kencana landfill. Corrosion rate for TPA Gunung Kupang case varies from 0.441 to 0.718 mmpy. Meanwhile, corrosion rate for TPA Cahaya Kencana varies from 0.131 to 0.495 mmpy. This is due to lower pH of leachate water from TPA Mount Kupang.